2016
DOI: 10.3389/fpls.2016.01695
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis and Identification of Genes Associated with Floral Transition and Flower Development in Sugar Apple (Annona squamosa L.)

Abstract: Sugar apple (Annona squamosa L.) is a semi-deciduous subtropical tree that progressively sheds its leaves in the spring. However, little information is available on the mechanism involved in flower developmental pattern. To gain a global perspective on the floral transition and flower development of sugar apple, cDNA libraries were prepared independently from inflorescent meristem and three flowering stages. Illumina sequencing generated 107,197,488 high quality reads that were assembled into 71,948 unigenes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 78 publications
6
46
0
Order By: Relevance
“…Subpetiolar buds are rare in Annonaceae, and this represents the first such observation in the tribe Miliuseae, although similar buds have previously been recorded in Annona (Soler & Cuevas, 2009;Liu & al., 2016). Wuodendron resembles Meiogyne and Sapranthus in its eucamptodromous leaf venation; this feature is common in the tribe Miliuseae, as well as the closely related tribes Monocarpieae (Mols & Keßler, 2000) and Dendrokingstonieae (Chaowasku & al., 2012b).…”
Section: Discussionsupporting
confidence: 78%
“…Subpetiolar buds are rare in Annonaceae, and this represents the first such observation in the tribe Miliuseae, although similar buds have previously been recorded in Annona (Soler & Cuevas, 2009;Liu & al., 2016). Wuodendron resembles Meiogyne and Sapranthus in its eucamptodromous leaf venation; this feature is common in the tribe Miliuseae, as well as the closely related tribes Monocarpieae (Mols & Keßler, 2000) and Dendrokingstonieae (Chaowasku & al., 2012b).…”
Section: Discussionsupporting
confidence: 78%
“…To investigate whether this type of gene is more widespread among the Annonaceae, we downloaded RNA-seq data from the NCBI Sequence Read Archive. These data were generated from RNA isolated from the mature flowers of Annona squamosa (Liu et al 2016) and leaves of Annona muricata (www.onekp.com). We assembled transcriptomes and searched them with tBLASTn using the pamAD transcript as the query sequence.…”
Section: Other Annomuricatin-like Peptidesmentioning
confidence: 99%
“…A GO and KEGG pathway enrichment analysis indicated that the common DEGs between EV vs. ER and LV vs. LR were enriched for circadian rhythm -plant and salicylic acid biosynthetic process (Fig. S6b), indicating that circadian rhythm and salicylic acid play an important role in the B. napus oral transition, which was also reported in the Annona squamosa and Rosa chinensis [40,41]. We also observed signi cant enrichment for genes involved in the circadian rhythm between LR vs. ER, suggesting that the owering time difference between early-and late-owering lines was primarily due to the expression difference of circadian rhythm genes (Fig.…”
Section: Identi Cation Of Owering Degsmentioning
confidence: 64%